A basque Melusine: "La dama de Vizcaya" - Prieto Lasa, J. Ramón (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
Proceeding from the oral tradition, some legandary narrations were incorporated to the Geneology of the Haro with the proposal to exalt and dignify the family history. As it is known, since the 13th Century it's a common practice of the cultural productions of determinated sectors of the European aristocracy. From the beginning of the articulation of one of the tales, La Dama de Vìzcaya, in different levels of signification, they express their most important units and the relations which establish different sectors (social, cultural, mythical...) of the activity and human thoughts
Keywords: Melusine; La dama de Vizcaya; Haro